Confined Space Fire Simulation in CFAST - HODÚLOVÁ, Dorota; GAŠPERCOVÁ, Stanislava (Transactions of the VŠB-Technical University of Ostrava, Safety Engineering Series, 2023)
The Consolidated Fire and Smoke Transport Model computer program is a two-zone fire simulation model that gives each layer a uniform room temperature and gas concentration. The paper highlights two model scenarios that differ in the use of fire protection equipment. the first model scenario features a smoke detector that influences the course of the fire by detecting and signalling its occurrence. In the second model scenario, there is no smoke detector and therefore the course of the fire is not affected by detection and signalling and subsequent intervention. This paper aims to compare the results between the temperature of the upper and lower smoke layer, and the height of the smoke layer in the two simulations.